2020
DOI: 10.7202/1070551ar
|View full text |Cite
|
Sign up to set email alerts
|

“The Very Unrecognizability of the Other”: Edith Stein, Judith Butler, and the Pedagogical Challenge of Empathy

Abstract: There is no standard definition of empathy, but the concept is assumed to be innately pro-social and teachable regardless of factors such as power dynamics or other manifestations of social injustice within a society. Such assumptions in discursive practices, whether academic, popular, or pedagogical, obscure the emergence of two important questions: What does it mean when we cannot empathize with another? And could it be that we may gain greater insight from the examination of empathy’s limits and failures th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Cultivating empathy for gender transformation or justice is important (Flood 2019). However, feminist and profeminist research has urged educators to approach this concept with caution (Kukar 2016). Hemmings (2012, 152), for example, distinguishes between (what she terms as) "bad" and "good" forms of empathy; where the former produces feelings of pity and sentimentality for the other and the latter seeks to transform hierarchical relations.…”
Section: Principle Two: Entering a Relation Of Affective Equivalencementioning
confidence: 99%
See 1 more Smart Citation
“…Cultivating empathy for gender transformation or justice is important (Flood 2019). However, feminist and profeminist research has urged educators to approach this concept with caution (Kukar 2016). Hemmings (2012, 152), for example, distinguishes between (what she terms as) "bad" and "good" forms of empathy; where the former produces feelings of pity and sentimentality for the other and the latter seeks to transform hierarchical relations.…”
Section: Principle Two: Entering a Relation Of Affective Equivalencementioning
confidence: 99%
“…As much masculinities research points out (see Flood 2019; Pease 2010), defensiveness and resistance are common responses when young men hear women's stories of suffering, but particularly when they are confronted with their complicity in this suffering. It is thus important not to assume that empathy (i.e., imagining standing in the shoes of others) is always pro-social or that it will always lead to pro-social outcomes (Kukar 2016). Given these complexities, there remains ongoing debate about the extent to which empathy is teachable-many feminists argue that we can never really know the other and that it is far more important for those who are seeking to empathize to engage in critical self-reflection on the limits of their self and "other" knowledge (see Boler 1997;Hemmings 2012); to recognize, as Ellsworth has argued (1992), that our knowledge of the other is always partial, interested, and potentially oppressive.…”
Section: Principle Two: Entering a Relation Of Affective Equivalencementioning
confidence: 99%
“…The next component is the ability to empathize. Empathy should be owned by everyone, because this ability usually appears at elementary school age or around the age of six (Kukar, 2020). What distinguishes an individual's feelings of empathy from others is the level of depth of feeling and how to show these feelings of empathy.…”
Section: Resultsmentioning
confidence: 99%
“…Pre-service teachers reported that empathy entails the willingness to understand the motives of others who do not belong to one's own social or cultural group as the opposite of mere self-interest. Common approaches in teaching diversity would involve positive representations of groups that are usually portrayed negatively in the dominant culture, facilitating empathy by didactic methods that allow students to "feel what it is like" to be marginalised (Kukar, 2016). Within transformative learning, learners arrive at this point when exploring the disorienting dilemma.…”
Section: Discussionmentioning
confidence: 99%